Optimization of synthesis of carbon nanotubes on iron impregnated activated carbon - Al-Sa'adi, Mohammed A.; Al-Mamun, Abdullah; Muyibi, Suleyman Aremu; Atieh, Muataz A.; Alam, Md. Zahangir; Sopyan, Iis; Ahmed, Yehya M. (2010)
The potential application of Carbon nanotubes (CNTs) in adsorption processes requires it to be attached to certain substrates. Attachment of (CNT) to powdered activated carbon (PAC) is expected to enhance its ability for many industrial applications such as water treatment, oil refining and gas storage. In this research, the (PAC) was impregnated with 5% weight IronIII ions. The Fe3+ impregnated (PAC) was used as a substrate catalyst for growth of CNTs in a chemical vapor deposition (CVD) reactor at a various reaction temperature and flow rates of both the hydrogen gas and carbon source. The yield of CNT was studied using Design expert software in order to determine the optimum production condition The product was characterized by FSEM and TEM to study the optimum catalyst impregnation percentage that gives the best CNT growth and distribution